Comparing the in-store use of smartphones between shoppers of generations X-Y-Z - Silveira, Paulo Duarte (2019)
This research aims to contribute to digital shopper marketing and omnichannel themes, by analyzing if the generations X (also called “13th generation”), Generation Y (also called “Millennials”) and Generation Z (also called “Centennials”) have different behaviors on the use of smartphones during their shopping journeys in bricks-and-mortar retail stores. For that purpose, an empirical quantitative study was conducted, via an online questionnaire. The questionnaire was applied to a sample of 913 individuals, corresponding to 27% of generation X, 44% from generation Y, and 29% from generation Z. There were found some differences between those generations regarding the actions made with the help of smartphones during the visit to the physical store. The main differences were found on the actions: checking for prices online on competitor websites; checking for prices online on the physical store own website; asking for advice with the help of the smartphone, showing pictures of products to store employees and on the use of smartphones to search online for coupons or discounts.